Soluble CCL5 Derived from Bone Marrow‐Derived Mesenchymal Stem Cells and Activated by Amyloid β Ameliorates Alzheimer's Disease in Mice by Recruiting Bone Marrow‐Induced Microglia Immune Responses123. (18th June 2012) - Lee, Jong Kil; Schuchman, Edward H.; Jin, Hee Kyung; Bae, Jae‐Sung
Abstract: Microglia have the ability to eliminate amyloid β (Aβ) by a cell‐specific phagocytic mechanism, and bone marrow (BM) stem cells have shown a beneficial effect through endogenous microglia activation in the brains of Alzheimer's disease (AD) mice. However, the mechanisms underlying BM‐induced activation of microglia have not been resolved. Here we show that BM‐derived mesenchymal stem cells (MSCs) induced the migration of microglia when exposed to Aβ in vitro. Cytokine array analysis of the BM‐MSC media obtained after stimulation by Aβ further revealed elevated release of the chemoattractive factor, CCL5. We also observed that CCL5 was increased when BM‐MSCs were transplanted into the brains of Aβ‐deposited AD mice, but not normal mice. Interestingly, alternative activation of microglia in AD mice was associated with elevated CCL5 expression following intracerebral BM‐MSC transplantation. Furthermore, by generating an AD‐green fluorescent protein chimeric mouse, we ascertained that endogenous BM cells, recruited into the brain by CCL5, induced microglial activation. Additionally, we observed that neprilysin and interleukin‐4 derived from the alternative microglia were associated with a reduction in Aβ deposition and memory impairment in AD mice. These results suggest that the beneficial effects observed in AD mice after intracerebral SC transplantation may be explained by alternative microglia activation. The recruitment of the alternative microglia into the brain is driven by CCL5 secretion from the transplanted BM‐MSCs, which itself is induced by Aβ deposition in the AD brain. Stem Cells 201230:1544–1555;